Entre macacos velhos e queerpiras: uma etnografia por entre as interfaces dos serviços comerciais de busca por parceiros online no interior paulista - Padilha, Felipe André (Universidade Federal de São Carlos, 2019)
This thesis is an ethnography of the social uses of applications for partner’s search in the countryside of Sao Paulo state, and argues that the social uses of digital media constitute themselves as mediatization devices of subjects. The research field is built from the network of connections that I establish with my interlocutors: men born between the decades of 1975 and 2000, of the popular classes, who live in the countryside of Sao Paulo and who use commercial services for partner’s search for gay men. From the connections between my interlocutors and the interfaces, I propose an ethnographic approach to the social uses of apps. The ethnography presents and analyzes the ways in which these technologies are shaped by the contexts in which they are used. Technology generates opportunities, but also consequences that the subjects are forced to deal with. The “digital” generates new questions, approaches, conditions and also contingencies for the field research. The thesis mobilizes a diverse set of perspectives on ethnography alongside and inside digital media and proposes an understanding of the field as a network and, far from seeking a complete answer, intends to break apart an emerging theoretical-methodological framework to deal with fields wholly or partially constructed by technology. The work seeks to investigate the underlying rationale behind the platforms. Drawing on cultural, historical and sociological sources, I present a history of commercial services for partner search that connects preexisting forms with those in digital media. The uses placed in empirical contexts show how the subjects mobilize the technology also to respond to the contingencies that surround them. The ethnography shows how for men, especially those who live their sexual experiences with other men in secret, the digital interfaces can be read as a private and safe environment, but which requires the subject to take an active control position on the social situation. The explored hypothesis is that the applications generate a procedure for social interactions and, in doing so, legitimize the practices that engender. Furthermore, as occurs with the interfaces, the subjectivities and procedures adopted for intersubjective interactions are also socially modeled and displaced by its uses, as far as the forms of interaction undertaken here are instrumentalized for partner’s search within a set of previously established and enforced standards. Since it is from the materiality of the interfaces that subjects recognize themselves, by generating a procedure for intersubjective relations, applications are also constituted as materialized fragments of subjectivity.
Keywords: Comunidades rurais; Aplicativos de busca por parceiros; Reconhecimento; Mídias digitais; Etnografia; Rural communities; Partner Search Apps; Recognition; Digital media; Ethnography; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS